2021
DOI: 10.21154/jtii.v1i1.63
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Karakter Rasa Ingin Tahu Siswa Pada Tema Struktur dan Fungsi Tumbuhan

Abstract: Tujuan penelitian ini siswa diharapkan dapat mengembangkan karakter rasa ingin tahu pada mata pelajaran IPA sehingga hasil belajar siswa dapat meningkat. Jenis penelitian yang digunakan yaitu kuantitatif dan deskriptif kualitatif. Rancangan penelitian yang digunakan yaitu dengan teknik claster random sampling. Pengumpulan data dilakukan melalui tes tulis dan wawancara dengan guru serta siswa. Analisis data dilakukan secara deskriptif kualitatif dari hasil nilai yang diujikan ke siswa. Hasil penelitian menunjuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
2
4
0
3
Order By: Relevance
“…In general, students with high curiosity can be identified by the questions asked to the teacher, answering questions asked by the teacher 13 . According to Jannah et al, students' understanding of curiosity is based on their need to look for problems they have, that is, they can produce insights that can be used by many people, especially to the extent that they play an important role in the learning process and to the extent that the material is taught to them through learning activities and students can play their imagination regarding the material taught by the teacher related to in-depth knowledge of everyday life 14 .…”
Section: Resultsmentioning
confidence: 99%
“…In general, students with high curiosity can be identified by the questions asked to the teacher, answering questions asked by the teacher 13 . According to Jannah et al, students' understanding of curiosity is based on their need to look for problems they have, that is, they can produce insights that can be used by many people, especially to the extent that they play an important role in the learning process and to the extent that the material is taught to them through learning activities and students can play their imagination regarding the material taught by the teacher related to in-depth knowledge of everyday life 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the test consists of pretest and posttest questions based on open ended questions with a total of 5 questions in the form of descriptions that are adjusted to the curiosity indicators, namely explorer, discover, adventurous, questioning, and absorption. The students have listening, speaking, reading and writing skills (Jannah et al, 2021) Giving test questions aims to determine the extent of students' curiosity about the material being taught. The test was given before (pretest) and after (posttest) the socioscientific based CIRC model treatment.…”
Section: Methodsmentioning
confidence: 99%
“…If a student is willing to explore various sources to get answers to every question that requires an answer, it is an indicator that the student in question already has the character of curiosity. This is important because students can directly read information from various sources, such as books, modules, textbooks, and so on (Fatkul et al, 2021). Based on this, it can be concluded that the strengthening of the character of curiosity in learning Indonesian is seen from four aspects, paying attention to the course of learning, asking questions, seeking information in discussion activities, and learning resources.…”
Section: Curiosity Character Strengtheningmentioning
confidence: 98%